2014
DOI: 10.1002/2013jc008979
|View full text |Cite
|
Sign up to set email alerts
|

Finescale parameterizations of turbulent dissipation

Abstract: This article (1) reviews and clarifies the basic physics underpinning finescale parameterizations of turbulent dissipation due to internal wave breaking and (2) provides advice on the implementation of the parameterizations in a way that is most consistent with the underlying physics, with due consideration given to common instrumental issues. Potential biases in the parameterization results are discussed in light of both (1) and (2), and illustrated with examples in the literature. The value of finescale para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
302
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(336 citation statements)
references
References 107 publications
27
302
0
Order By: Relevance
“…The disagreement of the GH model might be associated with the wave field in the SCS. Previous studies (Polzin et al, 1995;Wijesekera et al, 1993) have indicated that the predictions of the GH model would exhibit departure from the observed dissipation by more than 1 order of magnitude in regions where the wave field deviates from the GM spectrum. Thus, it is appropriate to examine the wave field in the SCS.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The disagreement of the GH model might be associated with the wave field in the SCS. Previous studies (Polzin et al, 1995;Wijesekera et al, 1993) have indicated that the predictions of the GH model would exhibit departure from the observed dissipation by more than 1 order of magnitude in regions where the wave field deviates from the GM spectrum. Thus, it is appropriate to examine the wave field in the SCS.…”
Section: Discussionmentioning
confidence: 92%
“…Assuming a balance between vertical advection and vertical diffusion for tracers, Munk (1966) reported that a global average diapycnal diffusivity of 10 −4 m 2 s −1 is required to maintain gross oceanic stratification and overturning circulation (Tsujino et al, 2000). However, diapycnal diffusivity from turbulent mixing in the open ocean thermocline only ranges from 5 × 10 −6 to 3 × 10 −5 m 2 s −1 (Gregg, 1998;Polzin et al, 1995). Therefore, it has been argued that elevated turbulent mixing concentrated over rough topography (Ledwell et al, 2000;Wu et al, 2011) would aid in explaining this discrepancy.…”
Section: Introductionmentioning
confidence: 99%
“…These parameterizations are based on the pioneering work of Gregg (1989) with important refinements provided by Polzin et al (1995), Gregg et al (2003) and others. Empirical relationships were determined using shear measured at the 10-m scale by specialized profiling systems (Sanford et al (1982), Schmitt et al (1988), Lueck (2002)).…”
Section: Estimates Based On Finestructure Shearmentioning
confidence: 99%
“…Conventional acoustic Doppler current systems resolve velocity variations to vertical scales of generally between 50-100 m (Polzin et al (1995), Thurnherr et al (2015)). To address resolution limitations of shear measurements, Polzin et al (2002) proposed an empirically derived transfer function that accounts for the loss of measured velocity variance at smaller vertical scales.…”
Section: Estimates Based On Finestructure Shearmentioning
confidence: 99%
See 1 more Smart Citation